ANALYSIS OF USE, AVAILABILITY OF PERSONAL PROTECTION EQUIPMENT (PPE) AND COVID-19 INFECTIONS CASE ON HEALTH WORKERS : A LITERATURE REVIEW - Putri, Alifia Fiarnanda; Adriyani, Retno; Haibah, Anizah Izzi; Hamedon, Titi Rahmawati (Journal of Public Health Research and Community Health Development, 2022)
ABSTRACT COVID-19 is an infectious disease caused by the SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) virus. During the pandemic, health workers have a higher risk of being exposed to the coronavirus. This study aims to analyze the availability and use of PPE for COVID-19 infection cases in health workers. This study used the scoping review method. Selected articles had been chosen by topic and inclusion criteria. Twenty-four articles were varied based on research locations in the US, China, Italy, Germany, Ethiopia, India, Pakistan, Nigeria, Australia, and Israel. Health workers have used PPE when handling specimens or patients with COVID-19 symptoms. The health workers were varied, including doctors, dentists, veterinarians, public health officers, nurses, pharmacists, and medical personnel who treat COVID-19 patients or not”the type of PPE widely used as masks. Health care facilities have provided PPE, but access, quality, and availability vary. Cases of COVID-19 infection in health workers varied, and the symptoms. PPE availability indirectly affects the high or low cases of COVID-19 infection in health workers, so the availability of PPE for health workers must be considered. ABSTRAK COVID-19 merupakan penyakit menular yang disebabkan oleh virus SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2). Selama pandemi, tenaga kesehatan memiliki risiko lebih tinggi terpapar virus corona. Tujuan dari penulisan ini yaitu menganalis ketersediaan dan penggunaan APD terhadap kasus infeksi COVID-19 pada tenaga kesehatan. Penelitian ini menggunakan metode scoping review. Artikel yang dipilih sesuai dengan topik dan kriteria inklusi. Didapatkan 24 artikel dengan lokasi penelitian di AS, Cina, Italia, Jerman, Ethiopia, India, Pakistan, Nigeria, Australia, dan Israel. Tenaga kesehatan telah menggunakan APD saat menangani pasien ataupun spesimen pasien dengan gejala COVID-19. Tenaga kesehatan yang diteliti bervariasi, meliputi dokter, dokter gigi, dokter hewan, public health officer, perawat, apoteker, tenaga medis yang menangani pasien COVID-19 ataupun tidak. Jenis APD yang paling banyak digunakan oleh tenaga kesehatan yaitu masker. Fasilitas pelayanan kesehatan telah menyediakan APD, namun akses, kualitas, dan ketersediaannya bervariasi. Kasus infeksi COVID-19 pada tenaga kesehatan bervariasi, begitu pula dengan gejala yang timbul. Penggunaan APD dapat meminimalisir risiko penularan COVID-19 pada tenaga kesehatan. Ketersediaan APD berpengaruh tidak langsung terhadap tinggi atau rendahnya kasus infeksi COVID-19 pada tenaga kesehatan, sehingga ketersediaan APD untuk tenaga kesehatan harus diperhatikan.